2014
DOI: 10.1039/c4ra00480a
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Carbon D–A strategy for [3 + 2] cycloadditions/annulations with imines: synthesis of functionalized pyrrolidines and related alkaloids

Abstract: [3 + 2] Cycloaddition/annulation: this article summarize the recent developments in synthesis of pyrrolidines and related alkaloids through complementary [3 + 2] cycloaddition/annulation of 1,3-carbon D–A precursors with imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…From these observations, it was concluded that in general, the reaction is dependent on the nucleophilicity of the N‐aryl moieties. Therefore, higher the electron rich character on the N‐heteroaryl part of imines higher is the reactivity, which ultimately leads to the lesser conversion of reactants into products and thus affects the yields considerably; results are in agreement with the reported reports [19]. However, the reactivity of the carbon of imine is governed more by steric factor rather than nucleophilicity.…”
Section: Resultssupporting
confidence: 90%
“…From these observations, it was concluded that in general, the reaction is dependent on the nucleophilicity of the N‐aryl moieties. Therefore, higher the electron rich character on the N‐heteroaryl part of imines higher is the reactivity, which ultimately leads to the lesser conversion of reactants into products and thus affects the yields considerably; results are in agreement with the reported reports [19]. However, the reactivity of the carbon of imine is governed more by steric factor rather than nucleophilicity.…”
Section: Resultssupporting
confidence: 90%
“…The catalytic asymmetric [3+2] cycloaddition of iminoesters with activated alkenes is undoubtedly an important synthetic reaction because it is one of the most straightforward and atom-economical methods for the enantioselective construction of five-membered carbocycles as well as heterocycles, which are structurally divers motifs in biologically active molecules and natural products. [13] Interestingly, although the importance of chiral pyrrolidines highlights the need for the development of asymmetric [3+2] cycloaddition reactions, [14] the first example of catalytic asymmetric 1,3-dipolar cycloaddition of iminoesters and alkenes was not reported until 2002. [15] Due to the difficulty of generating single isomers out of four possible diastereoisomers (classified as endo, exo, endo', and exo') in the 1,3dipolar cycloaddition of azomethine ylides and nitroalkenes, most of the ligands have been shown to be unsuccessful in achieving high enantioselectivity or diastereoselectivity.…”
mentioning
confidence: 99%
“…[47] Moreover, the 3D modification in such molecules is promoted by the isomerization process, [48] and the excellent sp 3 : sp 2 ratio enables the development of completely new organic molecules with improved biological properties. [49][50][51][52][53][54] With the simultaneous development of selective synthesis methods, numerous efforts have been made in drug discovery to exploit the important properties of the spiro-motif as natural products, [55][56][57] anticancer agents, [58][59][66][67][68][69] antiviral agents, [60] DNA alkylating agents, [61] antimycobacterial agents, [62,[75][76] anti-microbial agents, [63,66,73] antidiabetic, [64,70] AChE inhibitors, [65] anti-HIV, [71][72] antifungal, [73] antitumor, [74] antimalarial, [77] anti-inflammatory, [78] antitubercular, [79] HCV inhibitors, [80] sEH inhibitors, [81] cardiotonics, [82] also as vital drug molecules such as buspirone, [83] fluspirilene, [84] phloxine B, [85] and irbesartan [86] (Figure…”
Section: Introductionmentioning
confidence: 99%